2009
DOI: 10.1057/jibs.2009.82
|View full text |Cite
|
Sign up to set email alerts
|

Building a process model of local adaptation of practices: A study of Six Sigma implementation in Korean and US firms

Abstract: The strategic transformation of Asian firms into global players has involved the adoption and adaptation of many organizational practices developed in the West. We build a process model of adaptation by observing how an organizational practice is adapted to a local setting different from its locus of origin, through inductive methods and case studies of Six Sigma implementation in Korean and US firms. Based on these cases, we propose a cascading, sequential pattern to the local adaptation of the conceptual, so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
40
0
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(48 citation statements)
references
References 48 publications
5
40
0
3
Order By: Relevance
“…Second, related to the previous point, our analysis underscores the hybrid nature of language practices. Similar to other studies on hybridization of management practices (Ferner & Quantinalla, 1998;Gamble, 2010;Shimoni, 2011;Yu & Zaheer, 2010), our findings show that language policies and practices are hybridized precisely because they reflect both HQ and local practices. Our analysis adds to previous studies by showing large variations in this hybridization.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Second, related to the previous point, our analysis underscores the hybrid nature of language practices. Similar to other studies on hybridization of management practices (Ferner & Quantinalla, 1998;Gamble, 2010;Shimoni, 2011;Yu & Zaheer, 2010), our findings show that language policies and practices are hybridized precisely because they reflect both HQ and local practices. Our analysis adds to previous studies by showing large variations in this hybridization.…”
Section: Discussionsupporting
confidence: 88%
“…This means that any practice can become something different when it is put into use in a given context, often leading to a new kind of organizational 'praxis'a term that refers to the ensemble of various practices. Empirical research has shown how the transfer of organizational practices involve various kinds of local translations and even lead to new hybrid practices (Ferner & Quantinalla, 1998;Gamble, 2010;Shimoni, 2011;Yu & Zaheer, 2010). For example, Ferner and Quantinalla (1998) described how globalization pressures have led to "Anglo-Saxonization" of human resource management (HRM) practices, but due to various cultural and institutional factors, in a distinctive "German manner" in German subsidiaries.…”
Section: A Recontextualization Perspective On Language Policies and Pmentioning
confidence: 99%
“…Jensen and Szulanski (2004) conclude differently; they find that adaptation of practices significantly increases the stickiness of cross-border knowledge transfer and, hence, makes the transfer process more difficult. Yu and Zaheer (2010) find that adaptation may better suit practices that hold strong social dimensions, such as quality management and HRM practices, whereas practices that hold strong technical dimensions better suit conformity and adoption. Aoki (2008) points to two successful examples of kaizen transfer at Chinese plants where the foreign plants outperformed their Japanese sister plants.…”
Section: Adaptation Of Practices To Local Contingenciesmentioning
confidence: 93%
“…The influence of home country on company actions can manifest itself in their internationalization patterns 26 A. Panibratov and entry mode choices, employment practices, key account management, CSR policy, and many other aspects relevant for this study. Researchers found that although companies adapt some of their internal and external business practices to the local norms, some differences remain (Yu and Zaheer 2010). Studies also suggest that MNE actions are highly correlated with the COO institutional environment (Deephouse and Suchman 2008).…”
Section: Liability Of Foreignness and Country-of-origin Effectsmentioning
confidence: 99%